Evaluating local workforce development programs in Upstate New York, USA. (June 2018) - Balsas, Carlos J. L.; Swingruber, Anthony; Lin, Yen-Fu
Workforce development programs in the United States have increasingly focused on two critical approaches: Learning at work and experience as education. Workforce development programs are increasingly aimed at making territories more competitive by strengthening labor markets and helping to meet the needs of employers in significant sectors of the economy. Workforce development in Upstate New York is an important step forward in preventing the region from lagging behind other regions in the country. In this paper, we examine the role of the Capital Region Workforce Investment Board, a local workforce improvement board under the supervision of the New York State Workforce Investment Board. Specifically, we evaluate the impacts of the new Capital Region Workforce Investment Board's Program on the federally funded Workforce Investment Act of 1998 Adult Program priorities. Before-and-after analysis comparing the program outcomes in two four year periods, 2006–2009 and 2010–2013 are presented. The results of the new plan are mixed across several key performance indicators. Evidence shows that the new focuses increased the average earnings of program participants in a situation where employment rates decreased slightly. Significant industries for 2012–2022 are also reviewed.